Paul Newman a life - Levy, Shawn 1961- (Harmony Books, 2009)
In "Paul Newman: A Life," film critic and pop culture historian Shawn Levy gives readers the ultimate behind-the-scenes examination of the actor's life, from his merry pranks on the set to his lasting romance with Joanne Woodward to the devastating impact of his son's death from a drug overdose.
Keywords: Newman, Paul -- 1925-2008; Motion picture actors and actresses -- United States -- Biography; USA; Biografie